TORCH infection in antenatal women: A 5-year hospital-based study - Nirmal, Kirti; Saha, Rumpa; Ramachandran, V G; Khan, Amir Maroof (Eastern Journal of Medical Sciences, 2017)
Objectives: The diagnosis of acute TORCH infection in pregnant women being pertinent for the management of such infections prompted the current study due to lack of published data from India describing the seroprevalence of specific IgM antibodies to TORCH agents in this part of Northern India. Material and Methods: Blood samples of a total of 240 high-risk pregnant women attending the antenatal clinic of our tertiary care hospital during a 5-year period (2005–2009) were analyzed for specific IgM antibodies to Toxoplasma gondii, rubella, Cytomegalovirus (CMV), and combined herpes simplex virus (HSV) 1 and 2 by capture enzyme-linked immunosorbent assay. Results: Overall, seropositivity to TORCH infection in the present study was 98.8%. Seropositivity to T. gondii was 24.2%, rubella 9.2%, CMV 53.8%, and 11.7% were positive for combined HSV-1 and 2 infections. The average age of the study population was 27.5 years. Overall, 15.4% of women were seropositive for coinfections. Conclusion: The high seropositivity of 98.8% and presence of multiple infections seen in the present study communicate to all health authorities to screen routinely all pregnant women for TORCH infections for appropriate intervention in the proper management of these patients.